The EU Cooperation with South African Countries: Main Trends and Prospects for Development - Savchenko Maryna V.; Apeniuk Anna I.; Skladaniuk Darina M. (Bìznes Inform)
The article is devoted to the study of the current situation, outlining the main trends in cooperation between the European Union and the countries of South Africa and determining the prospects for its deepening. Attention is focused on the cooperation of the European Union in the economic, political and social spheres with the countries of South Africa. The evolution of interaction, including the impact of the colonial past on modern relations is considered, and the role of the EU as a key investor and trading partner for South Africa is analyzed. The authors substantiate the importance of the EU investments in the development of infrastructure, education, health care and technology, which contribute to economic growth and increase the competitiveness of local enterprises. Particular attention is paid to the Economic Partnership Agreement between the EU and the countries of South Africa (SADC EPA) and its impact on trade relations. Changes in the trade balance between the EU and South Africa, in particular the impact of the COVID-19 pandemic on exports and imports, are studied. Specific examples of cooperation with countries such as Namibia and Botswana are considered, and the impact of foreign investment on their economic development is analyzed. Prospects for further development of cooperation between the EU and the countries of South Africa in certain spheres are highlighted. In particular, the EU and South African countries can work together to remove trade barriers and promote investment; the EU can continue to provide development assistance to South African countries to help them achieve their objectives; strengthen its cooperation in the field of peace and security to help address the challenges facing Africa as a whole; cooperate in the fight against climate change and on the development of a sustainable economy. The article states that cooperation between the EU and South African countries can benefit both regions. Stronger cooperation can contribute to economic growth, development, peace, and security.